Assessment method development of informatization level for transport sector in Ukraine as a guarantee of its competitiveness - Парубець, Олена Миколаївна (Technology audit and production reserves, 2016)
With the rapid spread of information and communication technologies in various sectors of economic activity it should increase the informatization level of transport sector, without which it will be difficult in the future to ensure its competitiveness in national and international transport market. In this regard, the object of research in the article is information support of transport sector in Ukraine. The study found that the level of implementation and development of ICT and information management systems in the transport sector does not meet modern requirements and needs of the economy. Existing industry informatization programs are unable to provide a high level of efficiency of transport interaction with other sectors of the national economy, not to mention the development of transport and economic links with countries near and far abroad. The author developed a method of assessing the level of transport informatization using the computer program «Statistical Package for the Social Sciences». Based on the calculation of the integral factor of the transport sector informatization determined that the most important influence on its have using different modes of transport on the Internet, particularly in obtaining banking and financial services and the exchange of data on logistics, production plans, forecast demand. The lowest level has using Internet for e-procurement. Presentation and promotion of transport services in social networks are also at the low level. To create a common information space for transport processes and ensure their safety; implementation of effective intersectoral and interdepartmental interaction of information resources it is offered to create a network of transport supermarkets, which specific features are use of advanced transportation, logistics, information and communication technologies to improve the competitiveness of transport sector in Ukraine.